KOMUNIKASI BARU BIRO ARSITEK DI MASA PANDEMI DALAM PANDANGAN POSTKOLONIALISME HOMI K BHABHA - Gayuh Budi Utomo; Rully Damayanti; Dyan Agustin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2020)
Title: New Communication of The Architecture Firms in Pandemic Era; Following the Homi K Bhabha Post Colonial View A new order called the new normal is a central issue at this time. The period before the pandemic which became a standard value and became a reference suddenly was not compatible with the arrival of the Covid-19 pandemic outbreak. This is happening in Indonesia and around the world. Everyone is in a pandemic situation for a certain period time and there is no certainty that it will end. This of course also affects how to communicate in all aspects including the architectural bureau. New ways of communicating are carried out at architectural bureaus related to social distancing and physical distancing which are considered as effective prevention methods from the COVID-19 pandemic. The types of communication that have changed are communication with clients, communication with the team and communication with interns. There are significant differences in how to communicate from offline activities to online activities where we can still be connected both ways but not in the same place. This situation is a momentum to free the bonds of limitations that have occurred in terms of communication. We want to interpret this in the postcolonialism approach of Homi K Bhabha which is very relevant to the views of hybridity, ambivalence and the third space as a way of communicating new normal discourses.